Analisis Kinerja Belanja Daerah Pemerintah Kota Kupang Tahun 2018-2022 - Kusumaningrum, Yohana Gerardiana Ika; Manafe, Henny A.; Bibiana, Rere Paulina (EconBank: Journal of Economics and Banking, 2024)
ABSTRACT The purpose of this study is to seek the spending execution at the Kupang City Government in the 2018-2022 fiscal year can be said to be good in terms of the analysis of expenditure variance, analysis of expenditure growth, analysis of expenditure harmony and the ratio of expenditure efficiency. The instrument used is the analysis of shopping performance consisting of an analysis of shopping variants, an analysis of expenditure growth, an analysis of expenditure harmony and a ratio of expenditure efficiency. The results of the analysis presented is, a. The expenses execution in terms of analysis of expenditure variance can be said to be good because the implementation of spending is smaller than the budget, b. Expenses execution in terms of an analysis of expenditure growth in 2018-2019 the number of expenditure was increased and resulting positive, but in 2019-2022 the number of expenditure was decreased an resulting negative, c. The expenses execution in terms of analysis of the harmony of spending is more dominant operational expenditure than “modal” expenditure because operational expenditure is up to 90% above of total expenditure while “modal” expenditure is less than 10% of total expenditure, d. The expenses execution in terms of the expenses efficiency ratio can be said to be efficient because the criteria showed the results are below 100%. ABSTRAK Tujuan dalam penelitian ini adalah untuk mengetahui kinerja belanja pada Pemerintah Kota Kupang tahun anggaran 2018-2022 sudah dapat dikatakan baik ditinjau dari analisis varians belanja, analisis pertumbuhan belanja, analisis keserasian belanja dan rasio efisiensi belanja. Alat analisis yang digunakan adalah analisis kinerja belanja yang terdiri dari analisis varians belanja, analisis pertumbuhan belanja, analisis keserasian belanja dan rasio efisiensi belanja. Hasil analisis yang dikemukakan dapat diketahui bahwa, a. Kinerja belanja ditinjau dari analisis varians belanja sudah dapat dikatakan baik karean realisasi belanja lebih kecil dibandingkan dengan anggaran belanja, b. Kinerja belanja ditinjau dari analisis pertumbuhan belanja pada tahun 2018-2019 menunjukkan kriteria bernilai positif dan tahun 2019-2022 menunjukkan kriteria bernilai negatif, c. Kinerja belanja ditinjau dari analisis keserasian belanja lebih dominan belanja operasi dibandingkan dengan belanja modal karena belanja operasi pengeluarannya di atas 90% dari total belanja, d. Kinerja belanja ditinjau dari rasio efisiensi belanja sudah dapat dikatakan efisien karena pada kriteria tersebut besaran rasio pada kriteria tersebut di bawah 100%.